Civil engineering heritage: country profile – USA. Issue Volume 172:Issue EH 2(2019:May) (13th February 2019) - Friedman, Donald
Abstract : This paper is a review of the civil engineering heritage of the USA, one of a series of national profiles being published by Engineering History and Heritage . It is presented under five major headings: 'Major civil engineering achievements of the USA', 'Recognition of engineering heritage', 'Exemplar conservation of engineering structures', 'Information sources for engineering heritage' and 'References'. This profile discusses the development of civil engineering structures and examples of heritage importance in earthworks, canals, water supply, roads, railroads, bridges, tunnels and buildings.